The Cause of Premature Wind Turbine Bearing Failures: Overloading or Underloading?. Issue 5 (3rd September 2018) - Garabedian, Nikolay T.; Gould, Benjamin J.; Doll, Gary L.; Burris, David L.
ABSTRACT: Though the premature failures of wind turbine gearboxes are often attributed to bearing fatigue from overloading, there is compelling evidence that wear from underloading is a significant contributor. Here we attempt to gain insight into the relative contributions of over- and underloading by assessing planet bearing reaction forces from the Gearbox Reliability Collaborative (GRC) standard gearbox within a typical utility-scale wind turbine under realistic conditions. The results demonstrate that non-torque load sharing by the planetary stage increases and decreases planet bearing reaction forces at different locations within each rotor cycle regardless of wind speed. Planet bearing reaction forces exceeded the fatigue limit at wind speeds above 12 m/s and fell below the minimum load rating at wind speeds below 7 m/s. Based on analyses of published wind spectra from 10 U.S. sites, the expected fatigue life of the planet bearings ranged from 42 to 529 years even after accounting for non-torque load sharing. At the same 10 sites, planet bearings were underloaded (below 2% of the dynamic load rating) once per rotor cycle 40–70% of the time. Underloaded bearings are susceptible to surface damage when suddenly exposed to common transient events, such as yaw, wind gusts, braking, and grid faults. The resulting surface damage can initiate premature failure via wear (e.g., micropitting) or by reducing bearing fatigue life. The results suggest that carrier bearing clearance, non-torque load sharing, and planet bearing underloading are significant contributors to the premature failures of wind turbine planet bearings.